The role of algae in structuring reef communities: innovative monitoring and ecological insights within a Mediterranean conservation priority area - Thibaut de Bettignies; Lucie Vanalderweireldt; Marie Launay; Grégoire Moutardier; Vanina Pasqualini; Éric Durieux; Line Le Gall (Frontiers in Marine Science, 2025)
The Mediterranean Sea is a “sea under siege”, facing numerous anthropogenic pressures leading to the spread of invasive species and the degradation of reefs, particularly the reduction of habitat-forming macroalgae to turf algae or sea urchin barrens. The coastal waters of Corsica, often considered as a “reference state” due to their lower human impact, have not been thoroughly studied with regard to infralittoral reef communities. This study aimed to characterize these communities and identify their biotic and abiotic drivers through an innovative monitoring protocol (VIT-Reef). From 2019 to 2021, we monitored infralittoral reef communities at 59 sites between 15 and 35 m depth within and adjacent to three MPAs, using innovative rapid assessment dive surveys for 74 benthic taxa. Our results highlighted vertical zonation in reef communities, in particular the depth extent of photophilic algae and the emergence of pre-coralligenous communities. Important ecological implications of taxa covariation were discussed, such as the negative relationship between canopy-forming macroalgae and the invasive algae, Caulerpa cylindracea . Notably, geographical contrasts were observed along northern, southern and western MPAs, primarily influenced by algal community changes. Cystoseira (sensu lato) forests were identified as the climax state on western reefs, while northern and southern reefs showed significant cover of Dictyota spp. and crustose corallines respectively, with concerning levels of Caulerpa cylindracea in deeper southern reefs. Our results underscored the structuring role of Cystoseira spp. forests and the effects of light, nutrients and Posidonia oceanica meadows extending into the reefs. This study highlighted the role of algae in structuring reef communities and will contribute to establish a baseline for conservation planning and predicting future changes in these high priority infralittoral communities.

Levelling-up rhodolith-bed science to address global-scale conservation challenges - Fernando Tuya; Nadine Schubert; Julio Aguirre; Daniela Basso; Eduardo O. Bastos; Flávio Berchez; Angelo F. Bernardino; Néstor E. Bosch; Heidi L. Burdett; Fernando Espino; Cindy Fernández-Gárcia; Ronaldo B. Francini-Filho; et al. (Science of The Total Environment, 2023)

Concise review of the red macroalga dulse, Palmaria palmata (L.) Weber & Mohr - Pierrick Stévant; Peter Søndergaard Schmedes; Line Le Gall; Susse Wegeberg; Justine Dumay; Céline Rebours (Journal of Applied Phycology, 2023)
Palmaria palmata , commonly referred to as dulse , is a well-known and highly valued red macroalga distributed along the North Atlantic shores within a latitude range of approximately 40 to 80 °N. It is a species of commercial importance with historical records of use as food dating back several centuries to the current harvesting of dulse by hand-picking on the foreshore in Western Europe as well as Canada (New Brunswick and Nova Scotia) and USA (Maine). Because the demand for P. palmata increases and future sustainable commercial developments cannot rely solely on wild-harvested biomass, significant efforts have been made by research and industrial actors to cultivate the species. The low rates of spore release and germination, high mortality and epibiont contaminations remain major bottlenecks and point towards the need for optimized hatchery methods to enable upscaling the biomass production. The present review summarizes the available knowledge related to the biology, including the unique life history of the species among the Rhodophyta, the ecology as well as the nutrient composition and quality of P. palmata as food. Recent advances in taxonomy and cultivation techniques are reported along with a status of regulations for the commercial harvest of wild populations. An outlook on future industrial perspectives using biomass of P. palmata is also given.

Rhodolith Physiology Across the Atlantic: Towards a Better Mechanistic Understanding of Intra- and Interspecific Differences - Nadine Schubert; Viviana Peña; Vinícius W. Salazar; Paulo A. Horta; Pedro Neves; Cláudia Ribeiro; Francisco Otero-Ferrer; Fernando Tuya; Fernando Espino; Kathryn Schoenrock; Laurie C. Hofmann; Line Le Gall; et al. (Frontiers in Marine Science, 2022)
Coralline algae are important components in a large variety of ecosystems. Among them, rhodoliths are a group of free-living coralline red algae that cover extensive coastal areas, from tropical to polar regions. In contrast to other ecosystem engineers, limited research efforts preclude our understanding of their physiology, underlying mechanisms, drivers and potential differences related to species under varying environments. In this study, we investigated the photosynthetic and calcification mechanisms of six Atlantic rhodolith species from different latitudes, as well as intra-specific differences in one species from four locations. Laboratory incubations under varying light levels provided simultaneous photosynthesis- and calcification-irradiance curves, allowing the assessment of inter- and intra-specific differences on the coupling between these two processes. Stable isotope analysis and specific inhibitor experiments were performed to characterize and compare carbon-concentrating mechanisms (CCMs), as well as the involvement of specific ion-transporters for calcification. Our findings showed significant differences in rhodolith physiological mechanisms that were partially driven by local environmental conditions (light, temperature). High variability was found in the coupling between photosynthesis and calcification, in CCM-strategies, and in the importance of specific ion transporters and enzymes involved in calcification. While calcification was strongly correlated with photosynthesis in all species, the strength of this link was species-specific. Calcification was also found to be reliant on photosynthesis- and light-independent processes. The latter showed a high plasticity in their expression among species, also influenced by the local environment. Overall, our findings demonstrate that (1) rhodolith calcification is a biologically-controlled process and (2) the mechanisms associated with photosynthesis and calcification display a large variability among species, suggesting potential differences not only in their individual, but also community responses to environmental changes, such as climate change.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Diversity, distribution, and environmental drivers of coralline red algae: the major reef builders in the Southwestern Atlantic - Marina Nasri Sissini; Gabrielle Koerich; Maria Beatriz de Barros-Barreto; Luana M. Coutinho; Fernanda P. Gomes; William Oliveira; Iara O. Costa; José Marcos de Castro Nunes; Maria Carolina Henriques; Talita Vieira-Pinto; Beatriz N. Torrano-Silva; Mariana Cabral Oliveira; et al. (Coral Reefs, 2022)

Major loss of coralline algal diversity in response to ocean acidification - Viviana Peña; Ben P. Harvey; Sylvain Agostini; Lucia Porzio; Marco Milazzo; Paulo Horta; Line Le Gall; Jason M. Hall‐Spencer (Global Change Biology, 2021)
Calcified coralline algae are ecologically important in rocky habitats in the marine photic zone worldwide and there is growing concern that ocean acidification will severely impact them. Laboratory studies of these algae in simulated ocean acidification conditions have revealed wide variability in growth, photosynthesis and calcification responses, making it difficult to assess their future biodiversity, abundance and contribution to ecosystem function. Here, we apply molecular systematic tools to assess the impact of natural gradients in seawater carbonate chemistry on the biodiversity of coralline algae in the Mediterranean and the NW Pacific, link this to their evolutionary history and evaluate their potential future biodiversity and abundance. We found a decrease in the taxonomic diversity of coralline algae with increasing acidification with more than half of the species lost in high p CO 2 conditions. Sporolithales is the oldest order (Lower Cretaceous) and diversified when ocean chemistry favoured low Mg calcite deposition; it is less diverse today and was the most sensitive to ocean acidification. Corallinales were also reduced in cover and diversity but several species survived at high p CO 2 ; it is the most recent order of coralline algae and originated when ocean chemistry favoured aragonite and high Mg calcite deposition. The sharp decline in cover and thickness of coralline algal carbonate deposits at high p CO 2 highlighted their lower fitness in response to ocean acidification. Reductions in CO 2 emissions are needed to limit the risk of losing coralline algal diversity.

Coralline Algae in a Changing Mediterranean Sea: How Can We Predict Their Future, if We Do Not Know Their Present? - Fabio Rindi; Juan C. Braga; Sophie Martin; Viviana Peña; Line Le Gall; Annalisa Caragnano; Julio Aguirre (Frontiers in Marine Science, 2019)

Diversity of Chondracanthus (Gigartinaceae, Rhodophyta) on the Brazilian coast based on molecular and morphological evidences - Renato Rocha-Jorge; Fábio Nauer; Ingrid B. Silva; Mutue T. Fujii; Orlando Necchi; Line Le Gall; Mariana C. Oliveira (Brazilian Journal of Botany, 2018)

Patterns and drivers of species diversity in the Indo‐Pacific red seaweed Portieria - Frederik Leliaert; Dioli Ann Payo; Carlos Frederico D. Gurgel; Tom Schils; Stefano G. A. Draisma; Gary W. Saunders; Mitsunobu Kamiya; Alison R. Sherwood; Showe‐Mei Lin; John M. Huisman; Line Le Gall; Robert J. Anderson; et al. (Journal of Biogeography, 2018)
Aim Biogeographical processes underlying Indo‐Pacific biodiversity patterns have been relatively well studied in marine shallow water invertebrates and fishes, but have been explored much less extensively in seaweeds, despite these organisms often displaying markedly different patterns. Using the marine red alga Portieria as a model, we aim to gain understanding of the evolutionary processes generating seaweed biogeographical patterns. Our results will be evaluated and compared with known patterns and processes in animals. Location Indo‐Pacific marine region. Methods Species diversity estimates were inferred using DNA ‐based species delimitation methods. Historical biogeographical patterns were inferred based on a six‐gene time‐calibrated phylogeny, distribution data of 802 specimens, and probabilistic modelling of geographical range evolution. The importance of geographical isolation for speciation was further evaluated by population genetic analyses at the intraspecific level. Results We delimited 92 candidate species, most with restricted distributions, suggesting low dispersal capacity. Highest species diversity was found in the Indo‐Malay Archipelago ( IMA ). Our phylogeny indicates that Portieria originated during the late Cretaceous in the area that is now the Central Indo‐Pacific. The biogeographical history of Portieria includes repeated dispersal events to peripheral regions, followed by long‐term persistence and diversification of lineages within those regions, and limited dispersal back to the IMA . Main conclusions Our results suggest that the long geological history of the IMA played an important role in shaping Portieria diversity. High species richness in the IMA resulted from a combination of speciation at small spatial scales, possibly as a result of increased regional habitat diversity from the Eocene onwards, and species accumulation via dispersal and/or island integration through tectonic movement. Our results are consistent with the biodiversity feedback model, in which biodiversity hotspots act as both “centres of origin” and “centres of accumulation,” and corroborate previous findings for invertebrates and fish that there is no single unifying model explaining the biological diversity within the IMA .

How does molecular-assisted identification affect our estimation of α, β and γ biodiversity? An example from understory red seaweeds (Rhodophyta) of Laminaria kelp forests in Brittany, France - Marine Robuchon; Myriam Valero; Delphine Gey; Line Le Gall (Genetica, 2015)

Twenty years of observed and predicted changes in subtidal red seaweed assemblages along a biogeographical transition zone: inferring potential causes from environmental data - Régis K. Gallon; Marine Robuchon; Boris Leroy; Line Le Gall; Myriam Valero; Eric Feunteun (Journal of Biogeography, 2014)
Aim To assess environmental changes within a marine biogeographical transition zone and how they have affected seaweed assemblages and distributions over the past two decades. Location Brittany (western France, Europe) – a biogeographical transition zone between cold‐temperate and warm‐temperate regions. Methods We assessed spatio‐temporal variation for three environmental parameters [sea‐surface temperature ( SST ), suspended inorganic matter and chlorophyll a ] between 1992 and 2012 in five adjoining regions using generalized linear models. To investigate changes in assemblages and distributional patterns of red seaweeds based on sampling surveys conducted during two separate periods (1992–1998 and 2010–2012), we used two complementary approaches, multivariate data analysis and species distribution models ( SDM s) with a set of modelling procedures. Results Coastal water temperature in Brittany has increased by 0.7 °C on average over the past two decades (0.35 °C per decade). At a finer scale, changes in SST showed that Brittany constitutes a mosaic of contrasting conditions, with the western and north‐western regions being colder and less affected by climate change than the other three regions. Our results suggest that increasing SST caused significant changes in subtidal red seaweed assemblages over the 20‐year period. Between the two periods, SDM s predicted significant species shifts for seven out of ten representative species, and reductions in the distribution ranges of most species. Main conclusions Our study confirmed important differences across the different regions of the studied biogeographical transition zone. Changes in abiotic parameters and red seaweed assemblages are expected to occur at varying extremes across these regions, with western and north‐western Brittany representing the most stable zones that might constitute a potential refuge for certain species when responding to global changes.

Contrasting genetic diversity patterns in two sister kelp species co‐distributed along the coast of B rittany, F rance - Marine Robuchon; Line Le Gall; Stéphane Mauger; Myriam Valero (Molecular Ecology, 2014)
We investigated patterns of genetic structure in two sister kelp species to explore how distribution width along the shore, zonation, latitudinal distribution and historical factors contribute to contrasting patterns of genetic diversity. We implemented a hierarchical sampling scheme to compare patterns of genetic diversity and structure in these two kelp species co‐distributed along the coasts of B rittany ( F rance) using a total of 12 microsatellites, nine for L aminaria hyperborea and 11 for L aminaria digitata , of which eight amplified in both species. The genetic diversity and connectivity of L . hyperborea populations were greater than those of L . digitata populations in accordance with the larger cross‐shore distribution width along the coast and the greater depth occupied by L . hyperborea populations in contrast to L . digitata populations. In addition, marginal populations showed reduced genetic diversity and connectivity, which erased isolation‐by‐distance patterns in both species. As L . digitata encounters its southern range limit in southern B rittany ( SB r) while L . hyperborea extends down to mid‐ P ortugal, it was possible to distinguish the effect of habitat continuity from range edge effects. We found that L . digitata did not harbour high regional diversity at its southern edge, as expected in a typical rear edge, suggesting that refuges from the last glacial maximum for L . digitata were probably not located in SB r, but most likely further north. For both species, the highest levels of genetic diversity were found in the I roise S ea and M orlaix B ay, the two regions in which they are being currently harvested. Preserving genetic diversity of these two foundation species in these areas should, thus, be a priority for the management of this resource in B rittany.